Corticosteroid and Immunosuppressive Treatment in Glomerulonephritis - H. Alatas (Paediatrica Indonesiana, 1974)
On this occasion we would only re-view glomerulonephritis which is notassociated with systemic diseaseslike Schonlein Henoch purpura, Sys-temic lupus erythematosus etc.